1992
DOI: 10.1099/00222615-37-6-389
|View full text |Cite
|
Sign up to set email alerts
|

Character and origin of vacuoles induced in mammalian cells by the cytotoxin of Helicobacter pylori

Abstract: Summary. Cytotoxic activity of culture supernates of Helicobacter pylori is manifested by vacuolation of mammalian cells in vitro. The formation and maturation of toxin-induced vacuoles in HeLa cells has been studied to examine the possibility that they are autophagosomal in nature. Observation by light microscopy revealed that vacuoles originate in a perinuclear position, increasing in number and size until cell degeneration and lysis occur after 48 h. Ultrastructural study of mature vacuoles indicated the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
49
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 20 publications
5
49
0
2
Order By: Relevance
“…There is evidence that the autophagocytic pathway converges with the endosomal pathway at a prelysosomal level (37,38). On the basis ofmorphological exmination, vacuoles have been suggested to originate from endosomes (7) or autophagosomes (39,40). If this latter proposal were correct, increased autophagocytosis would enhance the effect of vacA.…”
mentioning
confidence: 98%
“…There is evidence that the autophagocytic pathway converges with the endosomal pathway at a prelysosomal level (37,38). On the basis ofmorphological exmination, vacuoles have been suggested to originate from endosomes (7) or autophagosomes (39,40). If this latter proposal were correct, increased autophagocytosis would enhance the effect of vacA.…”
mentioning
confidence: 98%
“…9,12,17 Several of the earliest studies describing the action of VacA on cultured epithelial cell lines reported that broth culture supernatants from vacA + H. pylori strains induced the formation of intracellular vesicles that visibly stained with acridine orange, initially excluded the endocytic marker Lucifer yellow, and, appeared to contain cytoplasmic content. 18,19 Although these are classical characteristics of autophagosomes, neither the capacity of H. pylori to induce autophagy nor the relationship of these autophagic-like vesicles to VacAdependent vacuoles has been systematically evaluated. Autophagy is an evolutionarily-conserved cellular mechanism for the degradation of cellular components in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, orally administered VacA induces gastric mucosa degeneration and inflammatory cell recruitment Marchetti et al, 1995). This toxin causes vacuolation of cells in culture (Leunk et al, 1988;Catrenich and Chestnut, 1992) and has therefore been named vacuolating cytotoxin (VacA) (Cover and Blaser, 1992). These vacuoles are acidic and their membrane contains the vacuolar ATPase proton pump and the small GTP-binding protein rab7; therefore, they have been suggested to arise from late compartments of the endocytic pathway (Cover et al, 1993;Papini et al, 1993;.…”
Section: Introductionmentioning
confidence: 99%